Optimasi Penggunaan NaOH dan Poly Aluminium Chloride pada Pengolahan Air Asam Tambang Batubara, Tanjung Enim, Sumatera Selatan - Alieftiyani Paramita Gobel; Nur Athiyya; Nadia Thereza; Muhamad Hidayatul Ilham; Chairunnisa Van Gobel (Yayasan Literasi Sains Indonesia, 2025)
High rainwater runoff in coal mining areas has a significant effect on the intensity of acid mine drainage (AMD) formation. Therefore, efforts to treat AAT during the rainy season by applying active methods must consider efficient and effective aspects. Based on these conditions, this study will analyze the aspects of using an effective dose of NaOH in neutralizing the degree of acidity (pH) of AAT and analyze the use of an effective dose of Poly Aluminum Chloride (PAC) according to environmental quality standards regulated in South Sumatra Governor Regulation No. 8 of 2012 concerning Quality Standards for Coal Mining Liquid Waste. Sampling of AAT is carried out at the inlet of the coal mining settling pond, then the AAT sample is carried out to improve quality using NaOH and PAC materials using the jar test method. The formulation of the optimum dosage of NaOH and PAC to improve the quality of AAT using linear statistical analysis with a range of water pH values of 6 - 9. The results showed that the quality of AAT at the inlet of the settling pond had an initial pH of 4.9 and TSS 3716 mgl-1 and after treatment using NaOH and PAC there was an increase in the quality of AAT with pH and TSS meeting the water quality standards that are safe to flow into the river.